Rječnička raznolikost pisanih tekstova osoba s razvojnim jezičnim poremećajem - Hržica, Gordana (Array, 2020)
Developmental language disorder (DLD) is one of the most common language disorders in preschool and school age, and it also persists later in life. Children with DLD show a range of expressive and/or receptive difficulties in language, including vocabulary acquisition. The goal of this research was to explore the differences between persons with developmental language disorder and persons with typical language development (TLD) in lexical diversity. Earlier research focused on spoken discourse of younger speakers. In the present research, written discourse of speakers covering a broad age range was explored. Twenty participants with DLD and 19 with TLD were selected from the Croatian Corpus of Non-professional Written Language (Kuvač Kraljević, Hržica and Kologranić Belić, in press). They produced narrative language samples based on the Expression, Reception and Recall of Narrative Instrument (ERRNI; Bishop, 2004). To measure lexical diversity, four measures were calculated: the number of different words (NDW) and type-token ratio (TTR) on a restricted number of words, the moving average type-token ration (MATTR) and lexical diversity D on full-length samples. The independent samples t-test was used to compare the two groups. Participants with DLD had significantly lower results on all four measures. This leads to the conclusion that all four measures can differentiate groups of participants with different language status. Persons with DLD showed difficulties in using vocabulary when producing written narratives, which is a demanding language production task.